Experiences of childhood play among different generations in Estonia - Ugaste, Aino (Frontiers in Education, 2023)
Play is an important part of child development, learning and the lives of children; however, access to the space and time necessary for play has dramatically changed in recent years. The aim of this study is to examine memories about childhood play from three generations of people in Estonia. Individual interviews were used to retrospectively explore perceptions of play with 98 respondents. The respondents mainly associated play memories with outdoor games that involved joy, fun, and excitement. The findings identified that freedom and a variety of options for play were important for children. The results highlighted the wide repertoire of play across generations and the difference between play for urban and rural children. The findings were compared with earlier studies and considered in light of educational and political changes in Estonian society.